The hacker and the state cyber attacks and the new normal of geopolitics - Buchanan, Ben (Harvard University Press, 2022)
"The threat of cyberwar can feel like something out of a movie: nuclear codes hacked, powerplants melting down, immediate crisis. In reality, state-sponsored hacking looks nothing like this. It's covert, insidious, and constant. Ben Buchanan reveals the cyberwar that's already here, reshaping the global contest for geopolitical advantage.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Geopolitik; Cyberterrorismus; Information warfare; Cyberattacke; Cyber intelligence (Computer security); Hacking / Political aspects; Cyberterrorism; Cyberspace operations (Military science); Cyberspace / Political aspects